Pengaruh Pemberian Ekstrak Etanol Daun Sisik Naga (Pyrrosia Piloselloides L.) terhadap Penurunan Kadar Kolesterol Total Mencit Hiperkolesterolemia: Effect of Dragon Scales Leaf Ethanol Extract (Pyrrosia Piloselloides L.) on Reducing Total Cholesterol Levels in Hypercholesterolemic Mice - Helmice Afriyeni; Nesya Indah Putri; Rosiana Rizal (Jurnal Sains dan Kesehatan, 2023)
Hypercholesterolemia is one of the risk factor for cardiovascular disease such as stroke, atherosclerosis and coronary heart disease. The purpose of this study was to determine the effect of ethanol extract of dragon scales leaves (Pyrrosia piloselloides L.) on reducing total cholesterol (TC) of test animals. The instrument to test was 25 male white mice were induced hypercholesterolemia by eating a high fat diet (MDLT) in around 14 days. The animals were declared as hypercholesterolemia if the total of cholesterol level (TC) more than 230 mg/dl. Then the Animals divided into five groups namely positive control, comparison (simvastatin), and the group given the test extract doses of 25, 50, 100 mg/kgBB. The treatment was given for 15 days, and TC level were checked on days 0, 5, 10 and 15. The data were analyzed by Two Way of ANOVA and continued with Duncan's test. The results showed that the dose of the tested extract and the duration of administration had a significant effect (p